CARDIOVASCULAR RISK IN MEN AGED 18-27 YEARS – RESIDENTS OF TASHKENT CITY - Mukhamedova M.G; Arnopolskaya D.I (Scholar Express Journals, 2024)
to determine the prevalence of cardiovascular risk factors in men of military age on the basis of primary health care institutions of the Republic of Uzbekistan and to assess cardiovascular risk.
Keywords: Young age; cardiovascular risk; SCORE